Pewne Rozwiązania dla Kołowych Płyt Trójwarstwowych Obciążonych na Krawędzi - Gołaś, J. (Engineering Transactions, 1971)
In this paper are determined the solutions for circular three-layer plates, freely supported on the entire circumference (1.2)1, loaded at the edge by condensed moments mr = 1 and by a pair of normal forces Nr = 1, (Fig. 1 and 2). Three-layer plates of the theoretical model given by N. J. Hoff [2] are taken into consideration.